Application of Graphene/Tetraphenylboron-Dopamine Modified Graphite Electrode for Selective Determination of Dopamine - Zhang, Jing; Liu, Chang; E, Yifeng; Yue, Jingli; Chen, Lianshan; Li, Donghui (Asian Journal of Chemistry, 2014)
A novel electrochemical sensor based on graphene and tetraphenylboron-dopamine electroactive material was developed for determination of dopamine which is correlative to some neurogenic disease. Graphene was synthesized by one-step liquid-phase exfoliation of graphite and the tetraphenylboron-dopamine was prepared by precipitation reaction on formation of ion association complex. The resultant electrode showed better performance in selectivity, sensitivity and narrow potential window comparing with bare graphite electrode and graphite electrode modified by tetraphenylboron-dopamine. In the presence of 1000-fold concentration interference of ascorbic acid and uric acid, the linear range for dopamine was successfully determined from 1 × 10-4 to 1 × 10-10 mol/L with a correlation coefficient of 0.9969. The detection limit was estimated to be 7.39 × 10-11 mol/L in 3 of signal to noise ratio (S/N = 3). According with successive measurements in 10 times, the relative standard deviation of all results for graphene/tetraphenylboron-dopamine /graphite electrode still kept in 1.83 %. Moreover, the graphene/tetraphenylboron-dopamine/ graphite electrode could be stored for 30 days in 4 ºC without sharply decrease of its electroactivity. All results clearly prove that this modified electrode is sensitive way for selective determination of dopamine.